INVESTORS’ PERSPECTIVE AND NEEDS IN THE PROCESS OF DEVELOPING A BUSINESS PLAN - Stankov, Biljana M; Roganović, Milijana; Marjanski Lazić, Sonja (International Journal of Economic Practice and Policy, 2016)
A business plan is a very important written document about the current state and future intentions of the company and it meets the information and other needs of a wide range of users, regardless of the size of the company and its organizational structure, or belonging to particular economic activity; regardless of the stage of the life cycle in which the company is located and the like . A business plan is written by the existing, established companies for different needs as well as by startup companies that are eager to show the profitability of the business venture and the success of business ideas realization. The business plan often stands out as a means to establish initial communication between entrepreneurs and financing sources, as well as for their initial meeting. The research problem relates to highlighting the business plan as a very powerful means in the hands of entrepreneurs in applying for obtaining the necessary financial resources. The subject of the research includes the analysis of the differences between the many users of a business plan with an emphasis on commercial banks, investment funds and private investors, as financiers of the business venture and the most important users. The aim of the research relates to highlighting the needs of investors and appreciation of their perspectives in the process of developing a business plan, because without a quality business plan investor is at risk of unsafe moving through a very uncertain and changing environment.